Episodic Arctic CO2 Limitation in the West Svalbard Shelf - Sanz-Martín, Marina; Chierici, Melissa; Mesa, Elena; Carrillo-de-Albornoz, Paloma; Delgado-Huertas, Antonio; Agustí, Susana; Reigstad, Marit; Kristiansen, Svein; Wassmann, Paul F. J.; Duarte, Carlos M. (Frontiers in Marine Science, 2018)
The European Sector of the Arctic Ocean is characterized by low CO2 concentrations in seawater during spring and summer, largely due to strong biological uptake driven by extensive plankton blooms in spring. The spring plankton bloom is eventually terminated by nutrient depletion and grazing. However, low CO2 concentrations in seawater and low atmospheric resupply of CO2 can cause episodes during which the phytoplankton growth is limited by CO2. Here, we show that gross primary production (GPP) of Arctic plankton communities increases from 32 to 72 % on average with CO2 additions in spring. Enhanced GPP with CO2 additions occur during episodes of high productivity, low CO2 concentration and in the presence of dissolved inorganic nutrients. However, during summer the addition of CO2 supresses planktonic Arctic GPP. Events of CO2 limitation in spring may contribute to the termination of the Arctic spring plankton blooms. The stimulation of GPP by CO2 during the spring bloom provides a biotic feedback loop that might influence the global role played by the Arctic Ocean as a CO2 sink in the future.